Peningkatan Hasil Belajar Matematika Materi Sifat-Sifat Bangun Datar Dan Bangun Ruang Melalui Strategi True Or False Pada Siswa Kelas VI Semester Genap SDN 009 Bonai Darussalam Kabupaten Rokan Hulu - Wiyatno, Hengki (Faculty Of Education, 2024)
The aim of carrying out this research is: to improve learning outcomes for class VI Mathematics students on the subject of Properties of Flat Shapes through the True Or False Strategy at SDN 009 Bonai Darussalam, Rokan Hulu Regency, Academic Year 2020/2021. The subject of this classroom action research is Mathematics, the main material is about the Properties of Flat Shapes using the True or False learning strategy, for class VI students at SDN 009 Bonai Darussalam, Rokan Hulu Regency, Rokan Hulu Regency, with a total of 16 students. The learning improvement research location is at SDN 009 Bonai Darussalam, Rokan Hulu Regency. When this research was carried out in two cycles, cycle I was 8 February – 11 February 2021, cycle II was 22 February – 25 February 2021. The results of this research were that learning with the True or False strategy had a positive impact in improving Mathematics learning outcomes regarding the characteristics of Characteristics of Flat Buildings in Class VI Students of SDN 009 Bonai Darussalam, Rokan Hulu Regency, Rokan Hulu Regency. This can be seen in Cycle I, of the 16 students who completed as many as 9 students (56.25%) and those who did not complete as many as 7 students (43.75%). Meanwhile, in Cycle II, there were 14 students who completed (87.50%) and 2 students (12.50%) who did not complete. So, after Cycle II was held, student learning outcomes increased by 31.25%.